Application of Base Force Element Method on Complementary Energy Principle to Rock Mechanics Problems. (20th May 2015) - Peng, Yijiang; Guo, Qing; Zhang, Zhaofeng; Shan, Yanyan
Abstract : The four-mid-node plane model of base force element method (BFEM) on complementary energy principle is used to analyze the rock mechanics problems. The method to simulate the crack propagation using the BFEM is proposed. And the calculation method of safety factor for rock mass stability was presented for the BFEM on complementary energy principle. The numerical researches show that the results of the BFEM are consistent with the results of conventional quadrilateral isoparametric element and quadrilateral reduced integration element, and the nonlinear BFEM has some advantages in dealing crack propagation and calculating safety factor of stability.